A Systematic Review and Meta-Analysis of Nerve Gap Repair: Comparative Effectiveness of Allografts, Autografts, and Conduits. Issue 5 (26th December 2022) - Lans, Jonathan; Eberlin, Kyle R.; Evans, Peter J.; Mercer, Deana; Greenberg, Jeffrey A.; Styron, Joseph F.
Abstract : Background: Ideal nerve repair involves tensionless direct repair, which may not be possible after resection. Bridging materials include nerve autograft, allograft, or conduit. This study aimed to perform a systematic literature review and meta-analysis to compare the meaningful recovery (MR) rates and postoperative complications following autograft, allograft, and conduit repairs in nerve gaps greater than 5 mm and less than 70 mm. A secondary aim was to perform a comparison of procedure costs. Methods: The search was conducted in MEDLINE from January of 1980 to March of 2020, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies were included whether they reported nerve injury type, repair type, gap length, and outcomes for MR rates. Thirty-five studies with 1559 nerve repairs were identified. Results: Overall MR for sensory and motor function was not significantly different between autograft ( n = 670) and allograft ( n = 711) across both short and long gaps. However, MR rates for autograft (81.6%) and allograft (87.1%) repairs were significantly higher compared with conduits (62.2%) ( P < 0.05) in sensory short gap repairs. Complication rates were comparable for autograft and allograft but higher for conduit with regard to pain. Analysis of costs showed that total costs for allograft repair were less than autograft in the inpatient setting and were comparable in the outpatient setting. Conclusions: Literature showed comparable rates of MR between autograft and allograft, regardless of gap length or nerve type. Furthermore, the rates of MR were lower in conduit repairs. In addition, the economic analysis performed demonstrates that allograft does not represent an increased economic burden compared with autograft.